Surgical Management of Liver Metastases from Colorectal Cancer: A Single-Surgeon Preliminary Findings Report - Doykov, Mladen; Kostov, Gancho; Dimov, Rosen (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: Colorectal cancer is a significant medical and social problem. Approximately half of the patients with colorectal carcinoma develop liver metastasis. Most commonly, they are identified during the diagnostic process or the initial surgery. After the diagnostics, only 15% of the cases are referred to receive radical surgery. Liver resection in patients with hepatic metastases is the only way to improve their survival. Objective: To introduce a surgical strategy used for the treatment of colorectal liver metastases. Materials and Methods: The study included 539 patients who underwent surgery for colorectal carcinoma in the Department of Surgery at University Hospital "Kaspela" during the period 2014–2020. This data was collected from the patients’ disease history. Results: Of the 539 patients with colorectal carcinoma, 74 (13.7%) were diagnosed with synchronous liver metastases. In 38 (51.3%) of the cases, the metastases were solitary, of which 21 were removed simultaneously and 17 at the follow-up stage. In 8 (10.8%) cases, more than one (2 to 3) solitary metastasis was established near the edges. They were also removed simultaneously. In 6 patients (8.1%), bi-lobar and peripherally localized solitary lesions were found, which were removed instantly and chemotherapy was administered. In 22 (29.7%) of the patients with multiple bi-lobar metastases, only a biopsy was performed, and surgery was carried out only in those affected by chemotherapy. Conclusion: The possibilities of simultaneous and stepwise liver resections were expanded by focusing on individual approach preferences and improving diagnostic methods, liver surgery techniques, and modern chemotherapy. This increased the survival rate of patients with colorectal liver metastases.